Use the graph below to answer the following question: What is the average rate of change from x = 0 to x = 4? (6 points) 0

1

4

8​

Answers

You should have 2 points

Well it sounds like you are doing volume so it is length time winth time high so times all the fraction

Step-by-step explanation:

The answer is B.-1

Step-by-step:

When you calculate the average rate of change of a function, you are finding the slope of the secant line between the two points. f(x) = x2 and f(x + h) = (x + h)2 Therefore, the slope of the secant line between any two points on this function is 2x + h.p explanation:

Step-by-step explanation:

_______

Good evening ,

_______________

f(1)=3 and f(3) = -1 so the average rate of change from x = 1 to x = 4 is 1.

Look at the photo below for more details,

________________________________

:)


Use the graph below to answer the following question:  what is the average rate of change from x = 1

Step-by-step explanation:

We'll use the slope formula as soon as we figure out the coordinates to plug into it!  At x = -4, the y value there is 4; the coordinate is (-4, 4).  At x = 1, the y value there is -1; the coordinate is (1, -1).  Plugging into the slope formula:

m=\frac{-1-4}{1-(-4)}=\frac{-5}{5}=-1

If you didn't pick up this, the "average rate of change" is the same exact thing as the slope.  It's -1.

it is b

Step-by-step explanation:

its b because there is a u over the x axis making it 1

21

Step-by-step explanation:21

 The correct option is (C) 2.

Step-by-step explanation:  We are given to find the average rate of change of the given graph from x = 1 to x = 3.

Let the graphed function be denote by y = f(x).

From the graph, we note that

f(1) = -3   and  f(3) = 1.

We know that

the average rate of change of a function g(x) from x = a to x = b is given by

A_v=\dfrac{g(b)-g(a)}{b-a}.

Therefore, the average rate of change of the graphed function from x = 1 to x = 3 is given by

A_v=\dfrac{f(3)-f(1)}{3-1}=\dfrac{1-(-3)}{3-1}=\dfrac{1+3}{2}=\dfrac{4}{2}=2.

Thus, the required average rate of change is 2.

Option (C) is CORRECT.

OPTION B

Step-by-step explanation:

As you can see in the graph, when x=1, y=3 and when x=4, y=0

Then, draw a line that cut the points (1,3) and (4,0), as you can see in the image attached, and calculate the slope (which represents the average rate of change of the function), with the following formula:

m=\frac{y_2-y_1}{x_2-x_1}=\frac{0-3}{4-1}=-1

Therefore, the aswer is the option B.


Use the graph below to answer the following question:  what is the average rate of change from x = 1
2 should be your answer


Do you know the answer?

Other questions on the subject: Mathematics

Mathematics, 21.06.2019, yasarhan2
x = -3y = -18step-by-step explanation: to solve by substitution, substitute one variable and solve for the other. then substitute again to find the remaining variable.x-1/3(3x-9) =...Read More
2 more answers
Mathematics, 21.06.2019, Kelbee781
3Step-by-step explanation:Let system security be A, program implementation be B and platform development be CThen:25 = A + B + C - AB - BC - AC + ABCwhere AB is system security and...Read More
1 more answers